2004
DOI: 10.1158/0008-5472.can-03-2760
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor δ Stimulates the Proliferation of Human Breast and Prostate Cancer Cell Lines

Abstract: The nuclear receptor peroxisome proliferator-activated receptor ␦ [PPAR␦/␤ (NR1C2)] has been implicated in colorectal carcinogenesis by various molecular genetic observations. These observations have recently been supported by studies of activation of PPAR␦ by pharmacological agents. Here we present the first report of the stimulation of breast and prostate cancer cell growth using PPAR␦ selective agonists. Activation of PPAR␦ with compound F stimulated proliferation in breast (T47D, MCF7) and prostate (LNCaP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
7
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 37 publications
8
142
7
1
Order By: Relevance
“…We found by in vitro assay that the growth of intestinal cells was stimulated by the introduction of PPARd cDNA (data not shown, our unpublished data), findings that are consistent with other reports that PPARd enhances the in vitro growth of breast and prostate cancer cells (Stephen et al, 2004). These results suggest that other positive and negative regulators could be simultaneously exerting their effects on cell growth.…”
Section: Discussionsupporting
confidence: 91%
“…We found by in vitro assay that the growth of intestinal cells was stimulated by the introduction of PPARd cDNA (data not shown, our unpublished data), findings that are consistent with other reports that PPARd enhances the in vitro growth of breast and prostate cancer cells (Stephen et al, 2004). These results suggest that other positive and negative regulators could be simultaneously exerting their effects on cell growth.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with a PPAR␤/␦-dependent mechanism, we demonstrated that induction of IL-1Ra secretion by rosiglitazone was abolished by transfection with a dominant-negative form of PPAR␤/␦. We showed further that a low concentration of GW-501516, a highly selective PPAR␤/␦ agonist (27,63,64), reproduced the stimulating effect of highdose rosiglitazone on IL-1Ra secretion. Taken together, these data demonstrate that rosiglitazone enhanced IL-1Ra secretion in a PPAR␤/␦-dependent manner and that this likely occurred because its relative affinity for PPAR isotypes was counterbalanced by the pattern of expression of PPAR isotypes in response to IL-1␤ stimulation.…”
Section: Discussionmentioning
confidence: 64%
“…However, there is considerable controversy regarding the safety of PPARβ/δ ligands due to contradictory reports in the literature, in particular those describing effects in cancer models. For example, ligand activation of PPARβ/δ is reported to increase proliferation of human liver, cholangiocarcinoma, breast and prostate cancer cell lines (Stephen et al 2004;Xu et al 2006a;Xu et al 2006b). In contrast, colon cancer cell lines fail to exhibit an increase in cell growth by PPARβ/δ in either the presence or absence of serum (Shimada et al 2002;Stephen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ligand activation of PPARβ/δ is reported to increase proliferation of human liver, cholangiocarcinoma, breast and prostate cancer cell lines (Stephen et al 2004;Xu et al 2006a;Xu et al 2006b). In contrast, colon cancer cell lines fail to exhibit an increase in cell growth by PPARβ/δ in either the presence or absence of serum (Shimada et al 2002;Stephen et al 2004). Additionally, more recently it was shown that two different PPARβ/δ ligands inhibit cell growth of human liver and colon cancer cell lines, independent of culture medium serum (Hollingshead et al 2007a).…”
Section: Introductionmentioning
confidence: 99%